Molecules of Murder : Criminal Molecules and Classic Cases - Emsley, John (Milton Road : Royal Society of Chemistry, 2016)
Molecules of Murder is about infamous murderers and famous victims; about people like Harold Shipman, Alexander Litvinenko, Adelaide Bartlett, and Georgi Markov. Few books on poisons analyse these crimes from the viewpoint of the poison itself, doing so throws a new light on how the murders or attempted murders were carried out and ultimately how the perpetrators were uncovered and brought to justice. Part I includes molecules which occur naturally and were originally used by doctors before becoming notorious as murder weapons. Part II deals with unnatural molecules, mainly man-made, and they too have been dangerously misused in famous crimes. The book ends with the most famous poisoning case in recent years, that of Alexander Litvinenko and his death from polonium chloride. The first half of each chapter starts by looking at the target molecule itself, its discovery, its history, its chemistry, its use in medicine, its toxicology, and its effects on the human body. The second half then investigates a famous murder case and reveals the modus operandi of the poisoner and how some were caught, some are still at large, and some literally got away with murder. Molecules of Murder will explain how forensic chemists have developed cunning ways to detect minute traces of dangerous substances, and explain why some of these poisons, which appear so life-threatening, are now being researched as possible life-savers. Award winning science writer John Emsley has assembled another group of true crime and chemistry stories to rival those of his highly acclaimed Elements of Murder.
Keywords: Toxicology